Idea Pembentukan Pemerintahan Ibn Khaldun dan Asas Pembinaan Kesultanan Melaka dari Kurun Ke-15 hingga 16: The Idea of Ibn Khaldun’s Governance, and the Base for the Construction of the Sultanate of Melaka from the 15th to 16th Centuries - Ismail, Noorilham; Abd Aziz, Mohd Kasturi Nor; Arsani, Zarifah (Journal of Al-Tamaddun, 2021)
This study focuses on the idea of Ibn Khaldun’s governance by focusing on the Sultanate of Melaka in the 16th century. The primary goal of this research is to demonstrate the development of the Melaka Sultanate through the lens of cycle theory, the spirit of asabiyyah, and the concept of ‘umran as defined by Ibn Khaldun. The timeline discusses the early establishment of the Sultanate of Melaka until its fall at the start of Portuguese colonisation in 1511. The study used Muqaddimah and Sulalat us-Salatin (Sejarah Melayu) as the main source for discussion of various ideas to explain Ibn Khaldun's ideas about the reign of the Melaka sultanate from the 15th century to 16 AD. The qualitative method-guided analysis concluded that the Melaka Sultanate was built in accordance with Ibn Khaldun's theory of one-time rule. Thus, the intertextual differences employed are expected to yield an authoritative and informative argument on the relationship between Ibn Khaldun's ideas and the construction of the Melaka sultanate in the 15th to 16th centuries AD.